2016
DOI: 10.1371/journal.pone.0162168
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor, Vestibular, and Reaction Time Tests in Mild Traumatic Brain Injury

Abstract: ObjectiveMild traumatic brain injury is a major public health issue and is a particular concern in sports. One of the most difficult issues with respect to mild traumatic brain injury involves the diagnosis of the disorder. Typically, diagnosis is made by a constellation of physical exam findings. However, in order to best manage mild traumatic brain injury, it is critically important to develop objective tests that substantiate the diagnosis. With objective tests the disorder can be better characterized, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 20 publications
1
57
2
Order By: Relevance
“…We determined that PER and median AS latency were significantly different between concussion/PCS and control groups (Table 3). This result is consistent with results of previous studies that found one or both of these parameters to be affected in concussion or PCS, 3,15,17,18,20,30 though there is considerable heterogeneity in the literature. Not surprisingly, both PER and median AS latency were selected as ANN inputs during sensitivity analysis.…”
Section: Key Saccade Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…We determined that PER and median AS latency were significantly different between concussion/PCS and control groups (Table 3). This result is consistent with results of previous studies that found one or both of these parameters to be affected in concussion or PCS, 3,15,17,18,20,30 though there is considerable heterogeneity in the literature. Not surprisingly, both PER and median AS latency were selected as ANN inputs during sensitivity analysis.…”
Section: Key Saccade Parameterssupporting
confidence: 92%
“…However, eye movements (specifically antisaccades [ASs]) have been shown to be abnormal in concussion and PCS patients and may be useful in the development of objective diagnostic and prognostic tools. 3,[15][16][17][18][19][20]30 Saccades are rapid, conjugate eye movements that serve to transition between 2 areas of focus. We considered 2 subtypes: prosaccades (PSs) and ASs.…”
mentioning
confidence: 99%
“…Many of the TWS patients also have experienced traumatic brain injury (TBI) and mild TBI (mTBI), which can also produce cognitive dysfunction and dizziness highlighting the role of this comorbidity . TBI and mTBI are a significant health issue which affects service members and veterans during times of both peace and war.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Video recordings of consenting patients before and after intervention help to further document these obvious alterations in ways that complement standardized neuropsychology testing. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Other investigators have also explored the relationship between vestibular dysfunction and cognitive dysfunction; [19][20][21][22][23][24][25][26][27][28] however, Gizzi and coworkers used the Neurobehavioral Symptom Inventory, and the Beck Depression Inventory and reported no causal connection between vestibular disorders and cognitive dysfunction. 28 They studied 200 patients with "dizziness""-half with a history of brain trauma and half without.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation